No Evidence That Cognitive and Physical Activities Are Related to Changes in EEG Markers of Cognition in Older Adults at Risk of Dementia - Laptinskaya, Daria; Küster, Olivia Caroline; Fissler, Patrick; Thurm, Franka; Von Arnim, Christine A. F.; Kolassa, Iris-Tatjana (Frontiers in Aging Neuroscience, 2021)
An active lifestyle as well as cognitive and physical training may benefit cognition by increasing cognitive reserve, but the underlying neurobiological mechanisms of this reserve capacity are not well understood. To investigate these mechanisms of cognitive reserve, we focused on electrophysiological correlates of cognitive performance, namely on an event-related measure of auditory memory and on a measure of global coherence. Both measures have shown to be sensitive markers for cognition and might therefore be suitable to investigate potential training- and lifestyle-related changes. Here, we report on the results of an electrophysiological sub-study that correspond to previously published behavioral findings. Altogether, 65 older adults with subjective or objective cognitive impairment and aged 60–88 years were assigned to a 10-week cognitive (n = 19) or physical training (n = 21) or to a passive control group (n = 25). In addition, self-reported lifestyle was assessed at baseline. We did not find an effect of both training groups on EEG measures of auditory memory decay or global coherence (ps > 0.288) and a more active lifestyle was not associated with improved global coherence (p = 0.381) . Results suggest that a 10-week unimodal cognitive or physical training and an active lifestyle in older adults at risk for dementia are not strongly related to improvements in electrophysiological correlates of cognition.